The relationship between maternal perception of social support and breastfeeding patterns - Elham Alidadi-Shamsabadi; Mitra Savabi-Esfahani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Breastfeeding is beneficial for the health of infants and mothers. It is a complex social behavior that may be influenced by social support. The study aimed to determine the relationship between perceived social support of breastfeeding women and their breastfeeding patterns. MATERIALS AND METHODS: The research was a cross-sectional study on 300 mothers with 6-month infants or younger who were selected randomly. The data collection tool consisted standard social support and breastfeeding patterns questionnaires. We analyzed data using descriptive and analytical tests and SPSS 18 at a significance level of < 0.05. RESULTS: The results indicated that 85%, 82.2%, and 38% of the infants were exclusively breastfed at 1 week, 4, and 6 months after delivery, respectively. The result of post hoc LSD test indicated that the mean number of supporters for mothers, who were in the 6th month of delivery, was significantly lower than other times (P = 0.001). The one-way analysis of variance indicated no significant difference between perceived satisfaction of social support at different periods after delivery (P = 0.92). Despite the present results, which indicated that the number of supporters and scores of satisfaction with support in exclusive breastfeeding were higher than other groups, the differences were not statistically significant. CONCLUSIONS: The mean number of supporters was less in women, who had 6-month-old infants, than mothers who had just given birth. It seems mothers with supplements and formula feeding patterns, such as breastfeeding mothers, may be supported to use these methods. Therefore, more studies are suggested on this field.